Comparison of transperineal and endoanal ultrasound in detecting residual obstetric anal sphincter injury. (26th August 2019) - Stuart, Andrea; Ignell, Claes; Örnö, Ann‐Kristin
Abstract: Introduction: Endoanal ultrasound is considered the gold standard when assessing the obstetric anal sphincter complex. Due to its relative intrusiveness and economic cost, other ultrasound modalities are on the rise, such as transperineal ultrasound with a convex probe. The aim of our study was to evaluate the agreement between endoanal ultrasound scores (EAUS score) and transperineal ultrasound scores (TPUS score) in assessing residual obstetric anal sphincter defects. Material and methods: Fifty‐nine women were examined 6 months after primary suturing of obstetric anal sphincter injury with two ultrasound modalities. A standardized scoring system analyzing the length, depth and radial extent of both the external (EAS) and internal (IAS) sphincter was used. Wexner fecal incontinence score was used to assess the patients' symptoms. Results: Transperineal ultrasound scores score showed a strong significant correlation with EAUS score during both pelvic floor relaxation and contraction: Spearman's rho [ r s ] = 0.74, P  < 0.001, and r s  = 0.77, P  < 0.001, respectively. For both EAS and IAS, significant correlations were found for all parameters, that is, length, depth and angle between both EAUS and TPUS. A statistically significant correlation was found between EAUS score and Wexner score ( r s  = 0.36, P  = 0.005). A significant correlation between the EAS‐EAUS score ( r s  = 0.36, P  = 0.005) and Wexner score was found, but no significance was found between IAS‐EAUS score and Wexner score ( r s  = 0.22, P  = 0.097). Significant correlations were found for Wexner score and TPUS score in resting state ( r s  = 0.36, P  = 0.01) and contracting state ( r s  = 0.28, P  < 0.05), and between Wexner score and EAS‐TPUS score in resting state ( r s  = 0.32, P  = 0.02). Conclusions: The results indicated a strong agreement between endoanal and transperineal ultrasound in assessing residual obstetric anal sphincter defects 6 months after primary suturing. Furthermore, a weak significant correlation was found between the ultrasound scores and the patients' Wexner fecal incontinence score.